2003
DOI: 10.1002/micr.10163
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ischemia and reperfusion injury in growing rats: Hypothermia and N‐acetylcysteine modulation

Abstract: Our objective was to evaluate intestinal ischemia-reperfusion injury in growing rats, modulated by hypothermia (I/RH) and N-acetylcysteine (NAC). We used 30 EPM-1 Wistar male rats, aged around 35 days, weighing 90 g. Rats were randomized into 5 groups with 6 animals in each: I/RH group, intestinal ischemia under hypothermia for 40 min and reperfusion for 30 min; I/RH-NAC group, same procedure but adding NAC (150 mg x kg(-1)), previously with ischemia; S-H group, topic hypothermia for 40 min, and observation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Experimental studies have shown that NAC improves ischemia-reperfusion injuries in various organs, such as the liver 42 and the bowels. 43 The impact of NAC has been widely evaluated during various renal ischemia-reperfusion conditions including CI-AKI and renal transplantation. 7 , 22 , 28 , 29 , 36 The improvement of kidney injuries seems to result from several mechanisms associating decreased oxidative stress, nitric oxide-inhibiting effect leading to vasodilation, and preventive decrease in cytokine production and in apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that NAC improves ischemia-reperfusion injuries in various organs, such as the liver 42 and the bowels. 43 The impact of NAC has been widely evaluated during various renal ischemia-reperfusion conditions including CI-AKI and renal transplantation. 7 , 22 , 28 , 29 , 36 The improvement of kidney injuries seems to result from several mechanisms associating decreased oxidative stress, nitric oxide-inhibiting effect leading to vasodilation, and preventive decrease in cytokine production and in apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…These include brain cooling, allopurinol, magnesium, minocycline, erythropoietin, insulinlike growth factor, MK-801, BAF (boc-aspartyl [OMe]-fluoromethylketone), topiramate, N-acetyl cysteine, and stem cells. 2,[19][20][21][22][23][24] Each of these therapies addresses one or more mechanisms involved in the multiple pathways contributing to brain injury as cited above. Of all of these potential therapies, brain cooling has the most experimental support.…”
Section: Neuroprotection For Hiementioning
confidence: 99%
“…In some experimental studies of ischemia and reperfusion 11,12,15 , the histopathological references used to measure protection were the classification of intestinal injury according to Chiu et al 25 and Ozdemir et al 23 , who used their own classification as parameters for histological evaluation. Montero et al 15 used the score proposed by Park et al 26 In the present study, we defined using the width and height of the intestinal villi obtained as parameters for the histological evaluation of the different groups.…”
Section: ■ Discussionmentioning
confidence: 99%
“…formation of free radicals in various organs, especially in phenomena involving oxidative stress [13][14][15][16] .…”
mentioning
confidence: 99%